SCIENTIFIC-METHODICAL PREREQUISITES FOR DEVELOPMENT OF THE STEEL COMPOSITIONS FOR INCREASE OF RESISTANCE OF HIGH-LOADED STAMPS OF COLD DEFORMATION - V. N. Fedulov (Литьë и металлургия)
The basis of perfecting of the known steels composition with the purpose of using for solving of concrete production problem, in particular increase of instrument resistance, are examined in the article.